Refugees' mental health during the coronavirus pandemic: Psychological distress and continued loneliness - Theresa Margareta Entringer; Jannes Jacobsen; Hannes Kröger; Maria Metzing (DIW Weekly Report, 2021)
Many people are suffering from the consequences of the coronavirus pandemic. Refugees, however, belong to one of the underpriviliged groups in many areas of society. They are more likely than average to live in overcrowded living quarters such as community housing and are thus exposed to a higher risk of infection. At the same time, even before the pandemic, they were more likely than average to experience severe psychological distress and could thus be particularly affected by it. This Weekly Report analyzes how the first months of the coronavirus pandemic impacted the mental health of refugees and shows that their psychological distress is still high in 2020. In addition, refugees continued to feel very lonely during this time. Refugees' mental health should therefore be monitored closely to be able to both combat increasing psychological distress and reduce existing loneliness, two factors important to successful integration.
Keywords: I14; 330; refugees; mental health; Covid-19; corona